PENGARUH PEMAHAMAN NILAI AGAMA ISLAM TERHADAP BUDAYA KERJA PEGAWAI NEGERI SIPIL DI KABUPATEN PASAMAN BARAT - Armida Sari, Jayanti; Frinaldi, Aldri; Syamsir, Syamsir (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2015)
The purpose of this reaseach to reveal how the West Pasaman regency’s civil servants’ understanding of Islamic values particularly those associated with; (1) sincerity, (2) patience, (3) piety and trust in working influence their work culture. This study uses a quantitative approach. Data is collected through questionnaire and documentation. Quantitative data analysis was performed through multiple regression analysis and partial. This reaserch indicates that (1) the comprehension of Islamic values including sincerity, patience, piety and trust in work at the same time influence the work culture with 38.9% contribution, which is considered low category. (2) Sincerity in work influences work culture at 11.5%, which is very low category. (3) Patience in work influences work culture at 25%, which is low category. (4) Piety and trust in work influence work culture at 31%, which is low category.